Liquidity, firm size, and financial performance: the moderating role of female directors in Indonesian industrial firms - Ineputri, Aprilia Loika; Santoso, Hadi (Jurnal Mantik, 2025)
This research examines how liquidity, firm size, and female directors affect the financial performance of industrial sector firms listed on the Indonesia Stock Exchange. Using the dependent variable of return on assets (ROA), the analysis considered liquidity (CR) and firm size (measured by total assets), alongside the moderating role of female representation on boards directors. The findings indicate that liquidity has a positive and significant impact on financial performance, supporting agency theory, signalling theory, and resource dependence theory. Meanwhile, firm size has a positive but insignificant effect on financial performance. However, women's presence on boards does not moderate the relationship between liquidity and performance, primarily due to their limited representation, which renders their role symbolic rather than impactful. In contrast, women’s presence on boards amplifies the influence of firm size on performance, indicating that female directors improve decision-making quality, monitoring effectiveness, and resource access in larger firms. These findings emphasise the significance of financial health, operational scale, and inclusive governance as crucial drivers of corporate success in Indonesia's industrial sector